ChemInform Abstract: The First Total Synthesis of the Antiplasmodial Alkaloid (.+‐.)‐Cassiarin C Based on a Microwave‐Assisted Thermal Azaelectrocyclic Reaction. Issue 24 (2nd June 2014) - Hibino, Satoshi; Choshi, Tominari; Tsuchiya, Yuhta; Nishiyama, Takashi; Hatae, Noriyuki; Nemoto, Hideo; Tazaki, Yoshinari
Abstract The synthesis of alkaloid (I) is achieved in six steps in 60% overall yield from dihydroxymethylchromanone.